Positive Interactions and Avoidant and Anxious Representations in Relationships with Parents, Friends, and Romantic Partners - Furman, Wyndol (J Res Adolesc, 2013)
We examined associations between positive interactions and avoidant and anxious representations in relationships with parents, friends, and romantic partners. Two hundred adolescents completed questionnaires, observations, and attachment interviews. From a between-person perspective, those adolescents with more positive interactions overall had less avoidant representations. Within persons, more positive interactions were relative to one’s own average level in relationships, the less avoidant representations were for that type of relationship. Adolescents were less anxious about a particular type of relationship if they have positive interactions in their other types of relationships. Finally, representations were primarily predicted by interactions in the same type of relationship; interactions in other relationships contributed little. The findings underscore the importance of examining representations of particular types of relationships.